Safety and Efficacy of Budesonide for Liver Transplant Immune Suppression: Results of a Pilot Phase 2a Trial. Issue 11 (19th August 2020) - Bari, Khurram; Shah, Shimul A.; Kaiser, Tiffany E.; Cohen, Robert M.; Anwar, Nadeem; Kleesattel, David; Sherman, Kenneth E.
Abstract : Despite adverse effects like hyperglycemia, new‐onset diabetes after transplant (NODAT), and infectious complications, corticosteroid use remains an important part of liver transplantation (LT) immune suppression. Budesonide, a synthetic corticosteroid, undergoes extensive first‐pass hepatic metabolism with only 10% systemic bioavailability, providing an opportunity for an improved toxicity‐therapeutic ratio. Although effective in the treatment of autoimmune hepatitis, the effects of budesonide for LT immune suppression are unknown. We conducted a single‐center phase 2a trial to study the safety and efficacy of budesonide immunosuppressive therapy. From July 2017 to November 2018, 20 patients undergoing a first LT received budesonide tapering doses (from 9 to 3 mg) for 12 weeks. Patients were compared with matched control patients who received prednisone from the same time period. Additionally, both groups received calcineurin inhibitors and mycophenolate mofetil. Outcome measures at week 24 included rates of biopsy‐proven acute cellular rejection (ACR), NODAT (hemoglobin A1c >6.4%), and infectious complications. In the budesonide arm, 1 patient developed ACR at week 5 and was removed from the study. Another patient stopped the study drug at week 8 due to persistent nausea. Rates of ACR were similar between the budesonide and control groups (5% versus 5%, P = 1.00). Three patients in the control group developed NODAT versus none in the budesonide group (15% versus 0%; P = 0.23). There were 6 infections in the control group compared with none in the budesonide group (30% versus 0; P = 0.02). These pilot data suggest that budesonide has the potential to be a safe and effective alternative to prednisone for LT immune suppression while reducing steroid‐induced infections and NODAT. Randomized controlled trials are required to validate these findings. Abstract : https://www.wileyhealthlearning.com/Activity2/7177046/Activity.aspx?parentActivityId=0